Validating and developing a new agility test for karate - Marjani, Mohammad Ebrahim (2013)
Karate is one of the most popular martial art styles in the world as well as a popular sport in Iran. Successful performance in karate requires high level of agility that enables the karateka (karate player) to avoid the opponent’s attacks, and to assume optimal position for efficient performance of karate techniques. In order to measure agility, karate coaches make use of general and available agility tests. However, there are many agility tests and coaches need to know which one is the best test for karate. Hence, the purpose of this study is to find the best and most appropriate validated agility test and to develop a new agility test for karate using Analytic Network Process (ANP). Data was collected from twenty one karate experts’ opinion with mean of age and standard deviation 40.3 ± 7.0 and years of coaching 13.05 ± 5.80. Results for the ANP analyses in reported that speed is the highest priority in agility and the best valid agility test for karate is SEMO test. Based on karate-specific movement patterns and components of ranked agility tests, a new test- Marjani Agility Test for karate is developed.